Antimicrobial Peptides Epinecidin-1 and Beta-Defesin-3 Are Effective against a Broad Spectrum of Antibiotic-Resistant Bacterial Isolates and Increase Survival Rate in Experimental Sepsis - Albert Bolatchiev (MDPI AG, 2022)
The antimicrobial peptides human Beta-defensin-3 (hBD-3) and Epinecidin-1 (Epi-1; by Epinephelus coioides) could be a promising tool to develop novel antibacterials to combat antibiotic resistance. The antibacterial activity of Epi-1 + vancomycin against methicillin-resistant Staphylococcus aureus (22 isolates) and Epi-1 + hBD-3 against carbapenem-resistant isolates of Klebsiella pneumoniae (n = 23), Klebsiella aerogenes (n = 17), Acinetobacter baumannii (n = 9), and Pseudomonas aeruginosa (n = 13) was studied in vitro. To evaluate the in vivo efficacy of hBD-3 and Epi-1, ICR (CD-1) mice were injected intraperitoneally with a lethal dose of K. pneumoniae or P. aeruginosa. The animals received a single injection of either sterile saline, hBD-3 monotherapy, meropenem monotherapy, hBD-3 + meropenem, or hBD-3 + Epi-1. Studied peptides showed antibacterial activity in vitro against all studied clinical isolates in a concentration of 2 to 32 mg/L. In both experimental models of murine sepsis, an increase in survival rate was seen with hBD-3 monotherapy, hBD-3 + meropenem, and hBD-3 + Epi-1. For K. pneumoniae-sepsis, hBD-3 was shown to be a promising option in overcoming the resistance of Klebsiella spp. to carbapenems, though more research is needed. In the P. aeruginosa-sepsis model, the addition of Epi-1 to hBD-3 was found to have a slightly reduced mortality rate compared to hBD-3 monotherapy.